Focal vibration of quadriceps muscle enhances leg power and decreases knee joint laxity in female volleyball players - Brunetti, O.; Botti, F. M.; Roscini, M.; Brunetti, A.; Panichi, R.; Filippi, G. M.; Biscarini, A.; Pettorossi, V. E. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: This double-blind randomized controlled study aims at determining the effect of repeated muscle vibration (rMV) on explosive and reactive leg power and on knee laxity of female volleyball players. METHODS: Eighteen voluntary volleyball athletes, belonging to the same senior regional level team (age=22.7±3 years, height=180.3 ± 5 cm, mass=64±4 kg) were assigned to three groups (N.=6) for vibration on contracted quadriceps (VC), vibration on relaxed muscle (VR), and sham vibration (NV), respectively. Intervention consisted in 3 rMV sessions performed in 3 consecutive days. In each session, 100Hz, 300-500 µm amplitude vibratory stimuli were bilaterally delivered to the quadriceps in three consecutive 10-minutes applications. Explosive and reactive leg power and knee joint laxity were evaluated 1 day before, and 1, 30, and 240 days after intervention. RESULTS: In VC group, explosive and reactive leg power increased respectively by ~16% and ~9% at 1 day, by ~19% and ~11% at 30 days and by ~26% and ~13% at 240 days, concomitantly knee laxity decreased by ~6%, ~15% and ~18% at the same times. These changes were significantly larger than in the other groups, in which leg power increment and knee joint laxity reduction remained close to ~3%, ~5% and ~10% at 1, 30 and 240 days, respectively. CONCLUSION: Combined bilateral voluntary contraction and rMV of the quadriceps muscles is a short-lasting, non-invasive technique that can significantly and persistently improve muscle performance and knee laxity in volleyball women players.